2008
DOI: 10.2528/pier08102702
|View full text |Cite
|
Sign up to set email alerts
|

Combined Beamforming With Alamouti Coding Using Double Antenna Array Group for Multiuser Interference Cancellation

Abstract: Abstract-This paper propose a new multiple-input multipleoutput (MIMO) signal processing scheme that combines optimum transmit and receive beamforming with the Alamouti space-time block code (STBC) transmission and modifies the decoding process. The scheme uses double antenna array groups to achieve stable performance regardless of direction of arrived (DOA) and angular spread (AS). In a multiuser MIMO communications scenario, the beamforming suppresses co-channel interference (CCI) by maximizing the uplink si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Various hybrid MIMO techniques scheme have been proposed in the past to improve the performance of wireless communication systems. Most of them focus on combining beamforming with diversity techniques [7][8][9][10]. However, this combined technique can only enable a system to achieve both diversity and beamforming gains.…”
Section: Introductionmentioning
confidence: 99%
“…Various hybrid MIMO techniques scheme have been proposed in the past to improve the performance of wireless communication systems. Most of them focus on combining beamforming with diversity techniques [7][8][9][10]. However, this combined technique can only enable a system to achieve both diversity and beamforming gains.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial research has shown the robustness of the blind adaptive array receiver algorithm, which is the combination of smart antenna and CDMA in wireless communications [7][8][9][10][11]. In [12], B. G. Agree developed Least-Squares Constant Modulus algorithm (LS-CMA) for multiuser systems in order to combat interuser interference (IUI) and separate cochannel signals.…”
Section: Introductionmentioning
confidence: 99%
“…An adaptive beamformer is collection of sensor elements whose outputs are combined by iteratively adjusted weight vector so as to pass a desired signal with minimum distortion while rejecting interfering signal. Since this form of array processing provides system antijam performance, it has become an essential requirement for the military and high resolution radars, communications and navigation systems [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%